The use of the balanced scorecard to enhance the organizational tourism position: An applied study of five-star hotels in Baghdad (Entrepreneurship Journal for Finance and Business, 2025)
The balanced scorecard plays a crucial role in enhancing the reputation of organizations in general, and specifically in the tourism sector, where performance evaluation is a key aspect of their operations. The main objective of this study is to adopt modern performance evaluation concepts to bring about a qualitative improvement in performance assessment, not only from a financial standpoint but also from other intangible perspectives. This research was motivated by the necessity to evaluate business performance in order to strengthen the competitive position of organizations in a challenging environment. The study was conducted in several high-end hotels in Baghdad, revealing a lack of clarity in performance evaluation methods and a failure to utilize the balanced scorecard, which negatively impacted the status of the hotels. The literature review employed a descriptive approach, exploring the relationship between the balanced scorecard and organizational status. A questionnaire was administered to a sample of 67 individuals (including directors, general managers, and department heads) to assess this relationship. The study yielded significant results, demonstrating a strong correlation between the balanced scorecard and the status of the organizations under investigation.